(untitled) (International Journal of Environmental Sciences, 2025)
The quality of water is the major concern survival of living being on earth. The groundwater quality of the mining regions is the most significant issues for the people. In the present study groundwater samples of coal mining areas of the Chhindwara district were collected in the different session and analyzed for water quality characteristics of different parameters such as pH, TDS (Total dissolved Solid), Electrical Conductivity (EC), Chlorides, Sulfate, Nitrate, Iron, Hardness, Magnesium, Sodium. The results obtained after analysis were compared with the different water quality standard such as IS and WHO. The obtained results indicate that the quality of the groundwater was more or less affected by the mining activities.